Analisa Pengaruh Corporate Governance Terhadap Praktik Earnings Management - Waisiyana Sastrawati; Saarce Elsye Hatane (Business Accounting Review, 2017)
The research on the affect of corporate governance to earning management had been done previously with inconsistent results. Nevertheless, there were no research about corporate governance which was measured by its internal mechanism, specifically the effect of board structure on earning management. This study aimed to examine the affect of corporate governance (board composition, board meeting and board size) on earning management.Board composition is the percentage of non-executive directors in board, board meeting is the number of meeting attended by board annually and board size is the number of members in board of directors. On this study also involved two control variables of firm size and return on assets (ROA). This study was done on companies in consumer goods and trade sectors listed in Indonesia Stock Exchange (IDX) during the period of 2011-2015 with the sample of 251 observation. The results showed that board composition and board size had negative influence on earning management, while board meeting had no influence on earning management. As for the control variables, firm size had no influence on earning management while ROA had positive influence on earning management.